Governance of Relationship Risks in Megaprojects: A Social Network Analysis - Linlin Xie; Ting Han; Martin Skitmore (Advances in Civil Engineering)
Megaprojects usually involve an alarmingly large number of stakeholders that form a complicated social network and lead to significant relationship risks to client/owners. Therefore, it is necessary to carry out megaproject risk management from a sociological point of view. Based on a case study of the Zhuhai Port, which connects Hong Kong, Zhuhai, and Macao, this paper analyzes the relationship risk between stakeholders and corresponding risk management strategies using social network analysis (SNA). The findings show that stakeholders with a lower density and higher centrality in the network have comparatively a lower relationship risk. Different stakeholders should choose appropriate partners to improve their centrality, reduce the network density to increase their ability to access resources, and enhance their influence and independence in the network. For megaproject client/owners, identifying and monitoring key stakeholders is the key to effective relationship risk governance. The findings provide a number of practical implications for relationship risk management and further demonstrate the importance of stakeholder teamwork, particularly for megaprojects.